Social media, lifestyle influence, brand awareness mediate Fore Coffee purchase decisions - Cristianto, Dwi Adnes Julians; Listiana, Erna; Afifah, Nur; Juniwati, Juniwati; Mayasari, Endah (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of social media marketing and lifestyle on purchase decisions, with brand awareness as a mediating variable. The methodology used is a causal research design. 225 respondents who are Indonesian consumers of Fore Coffee were given questionnaires to complete in order to gather data. The measurement model and structural model of the research construct being constructed are evaluated and analyzed in this study using Structural Equation Modeling (SEM) analysis with the aid of the statistical tool AMOS 24. In this research, the independent variables are social media marketing and lifestyle, the dependent variable is purchase decision, with brand awareness as the mediating variable. Variables are measured using 5-point Likert scale, where respondents are asked to rate their agreement with statements related to each variable. This study shows that social media marketing, lifestyle and brand awareness significantly influence purchase decisions directly and indirectly through brand awareness.